Acute toxicity of endosulfan to immature and adult Gastropods Lymnaea Radix cor ( Annandale and Prashad , 1919) - ojs_admin (University of Thi-Qar Journal of Science, 2019)
Endosulfan, polycyclic organochlorine pesticide contaminating aquatic ecosystem as a potential toxic pollutants, was investigated in the present study for acute toxicity. The immature and adult gastropods Lymnaea Radix cor were selected for the bioassay experiments. The 96 h LC 50 2were determined for the both stages. Data obtained from endosulfan acute toxicity tests were evaluated using the Probit Analysis Statistical Program. The 96h LCfor immature and adult snails were estimated as, (0.38) and (0.91) mg/l, respectively.